Complicated oesophageal duplication cyst in a 55-year-old man: a rare case from Pakistan - Khawaja, Arham Amir; Javaid, Arif; Qadri, Haseeb Mehmood; Hussain, Nuzhat Faqir; Yousaf, Pashmal (Journal of the Pakistan Medical Association, 2025)
Duplication cysts are congenital anomalies that arise during early embryonic development. They occur in the small intestine, oesophagus, stomach, and colon. Oesophageal duplication cyst (ODC) is rare among new-borns, but even rarer in adults. We report the case of a 55-year-old male with the presenting complaints of haematemesis, dysphagia, and significant weight loss for the past eight months. Clinical examination was unremarkable, except that the patient had pallor. Computed tomography scan confirmed the presence of ODC. Subtotal oesophagectomy with gastric pull-up and sub-aortic oesophagogastrostomy was completed. Histopathology was consistent with foregut duplication cyst. Post-operative period was complicated by left basal atelectasis, and the patient was discharged without long-term sequelae. Adult ODC can be regarded as a diagnosis of exclusion after ruling out oesophageal malignancy, high-grade oesophageal varices, mediastinal masses, and submucosal lesions. Complete surgical excision with restoration of gut continuity is optimal management in complicated, large (>5cm) ODC. Keywords: Oesophageal cyst, Oesophagectomy, Dysphagia, Jejunostomy, Pakistan.